Mapping the Conceptualization of Gender in Gambling Literature: A Scoping Review - Kairouz, Sylvia; Sowad, Abu Saleh Mohammad; Lambo, Lesley; Le Mesurier, Julie; Nadeau, Jessica (Critical Gambling Studies)

(untitled) (University of Alberta Library, 2023)
This scoping review aims to map the existing conceptualization of gender in peer-reviewed gambling scholarship to locate areas of future inquiry for a comprehensive understanding of the relationship between gender and gambling. It follows Arksey and O'Malley's (2005) framework for scoping reviews, updated by Levac et al. (2010) and Daudt et al. (2013). We located the relevant literature published between 2000-2020 by searching through eight academic databases using Boolean operators and various key search terms, yielding 31,533 results. After a thorough screening based on inclusion/exclusion criteria and excluding duplicates, we located 2,532 journal publications that addressed gender and gambling. Among them, 53.4% used gender as a descriptive demographic variable, 44.3% explored the comparative analysis between men’s and women's gambling behaviors, preferences, and risks, and only 2.3% focused on gender from a socio-cultural perspective. When articles mentioned gender, we found that it was primarily considered a descriptive demographic variable and an indicator of comparative analysis between men and women. Furthermore, the few articles that discussed the socio-cultural aspects of gender were mainly limited to a binary construction of gender. This scoping review concluded that there is a scarcity of socio-cultural studies of gender in gambling scholarship, indicating the need to expand socio-cultural analysis in research on gender and gambling.